The Ideal Concept of Fair Law Formation in Indonesia: The Application of Pancasila Values as a Philosophical Foundation at Every Stage of Law Formation - Risman Setiawan; Haris Yusuf; Idaman Idaman (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Within the hierarchy of legislation, laws, as one sort of legislation, have a critical position and carry a great deal of responsibility. The intellectual underpinning that integrates Pancasila ideals as the legal ideal and the manifestation of justice is one of the key pillars upon which laws are formed. Objective: This research aims to find the ideal concept of fair law-making. Method: This research is a normative legal study, which is a legal study conducted by examining library materials using existing literature as the object of study, including books, journals, and regulations related to the discussion of the problem, making this writing also a library research. Result: It is imperative that the principles of Pancasila be implemented throughout the entire legislative process, including the stages of academic, political, and legal text creation. As a philosophical underpinning, Pancasila ideals must be consistently applied throughout all of these stages. Conclusion: The ideal concept of law formation is necessary to create fair laws, and this ideal concept is to continually use Pancasila values as a philosophical foundation that incorporates the value of justice at every step of law production. These phases comprise the development of the legal, political, and academic manuscripts. Keywords: Legislation; Philosophical Foundation; Pancasila